2019
DOI: 10.1371/journal.pgen.1008268
|View full text |Cite|
|
Sign up to set email alerts
|

The Airn lncRNA does not require any DNA elements within its locus to silence distant imprinted genes

Abstract: Long non-coding (lnc) RNAs are numerous and found throughout the mammalian genome, and many are thought to be involved in the regulation of gene expression. However, the majority remain relatively uncharacterised and of uncertain function making the use of model systems to uncover their mode of action valuable. Imprinted lncRNAs target and recruit epigenetic silencing factors to a cluster of imprinted genes on the same chromosome, making them one of the best characterized lncRNAs for silencing distant genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 52 publications
4
59
0
Order By: Relevance
“…To understand how lncRNAs could target such large genomic regions, the roles of chromosome folding, lncRNA abundance, and CpG islands in the targeting of Airn and Kcnq1ot1 lncRNAs was assessed in trophoblast stem cells [51]. The authors found that chromosome folding brought distal regions into close proximity of the transcribed lncRNA on the paternal allele [51], consistent with allelic differences in folding of the Airn/Igf2r locus seen in vivo [45]. CpG islands, in particular, enabled PRC targeting and spreading along the silenced paternal alleles within these imprinted domains [51].…”
Section: Imprinted Gene Clustersmentioning
confidence: 88%
See 2 more Smart Citations
“…To understand how lncRNAs could target such large genomic regions, the roles of chromosome folding, lncRNA abundance, and CpG islands in the targeting of Airn and Kcnq1ot1 lncRNAs was assessed in trophoblast stem cells [51]. The authors found that chromosome folding brought distal regions into close proximity of the transcribed lncRNA on the paternal allele [51], consistent with allelic differences in folding of the Airn/Igf2r locus seen in vivo [45]. CpG islands, in particular, enabled PRC targeting and spreading along the silenced paternal alleles within these imprinted domains [51].…”
Section: Imprinted Gene Clustersmentioning
confidence: 88%
“…In somatic tissues, the extent of imprinting is restricted to a 'core' subset of genes within relatively close proximity to the gDMRs. However, in the placenta, numerous genes, as far away as 7.7 megabases (Mb), are silenced on the paternal allele ( Fig 2B) [36,37,39,43,45]. To date, placental-specific imprinted gene expression has been observed for 15 genes distal of Kcnq1ot1/Kcnq1 and 12 genes distal of Airn/Igf2r (Fig 1).…”
Section: Imprinted Gene Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…For some non-canonical imprinted genes (Smoc1, Jade1, Sfmbt2), it has recently been shown that the H3K27me3 imprint is lost during preimplantation development and through an unknown mechanism the imprint is transferred into a secondary DNA methylation imprint (39). By contrast, the Kcnq1 cluster, the Igf2r-Airn clus-ter and the Magel2 region of the Snrpn cluster gain H3K27me3 in post-implantation tissues, dependent on the germline DMR imprint (39), and for the Kcnq1 and Igf2r-Airn clusters through the action of imprinted long noncoding RNAs (40)(41)(42)(43). Interestingly, Dnmt1 knockout studies have shown that while imprinting of genes located centrally in the Kcnq1 cluster is maintained via germline DMR methylation, genes affected by maternal deletion of Smchd1, Tssc4 and Ascl2, are maintained via histone modifications (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence has indicated that, rather than being transcriptional noise, lots of non-coding RNAs (ncRNAs) can affect the expression levels of target genes [7,8]. Long non-coding RNAs (lncRNAs), one of a ncRNAs, which play critical roles in transcription, splicing and translation [9]. However, up to now, compared with mRNAs, the function of lncRNAs has not been well annotated [10,11].…”
Section: Introductionmentioning
confidence: 99%